Women’s Ready-to-Wear Collection with the Influence of Cottagecore - Grasheli Kusuma Andhini; Katharina Rossa Dewayanti (Mudra Jurnal Seni Budaya, 2023)
This study aims to understand the cottagecore aesthetic and its relationship to fashion, especially the extent to which it could act as a form of self-expression and coping mechanism. This research used an exploratory descriptive research approach with the application of interview, observational research and pattern exploration. Samples were chosen non-random and purposively aiming on the representative values and perspectives. Taking inspiration from Netflix’s series ‘Anne with an E’, which has comparable aesthetics to the cottagecore movement, this study took a modern approach on the cottagecore aesthetic to produce more wearable and versatile ready-to-wear pieces while retaining the principal elements and traditional techniques. It is found that the cottagecore aesthetic may appear to have arisen as a trend during the pandemic. However, as people are now seeking to be more sustainable, the cottagecore concept, which promotes slow living in connection with nature and appreciating craftsmanship, can continue to be prioritized in the future. Overall, this study offers pieces that boost people’s moods and transport them to a bucolic pastoral fantasy while aiming on better suit the current local market preferences.